Empowering community for slope information crowd-sourcing and monitoring based on web GIS - Eddie, Farah Hijanah (2018)
Landslide tragedies occurred in Taman Bukit Mewah, Bukit Antarabangsa on 6th December 2008. This traumatised the local residents and helped trigger awareness on supervision and monitoring of early signs of landslide in the residential area. This study’s goal is to facilitate local residents in gaining local knowledge and preparations for possibilities of landslides. This study aims to integrate the GIS web-based technologies with GIS community involvement in the use of the GIS portal. GIS community is a social unit of people living in the same area and at the same time, sharing spatial information among them. The GIS website display online map for Bukit Antarabangsa’s area, to facilitate users, especially the local residents to search, view and learn about the area, including the map and attributes information about slopes, hills, residential lots, roads and water drainage. In addition, map can be printed directly through GIS website. The daily rainfall information from Department of Irrigation and Drainage is integrated in the system; the total rainfall for the area is displayed. This is important as rainfall is one of the factors driving to landslide. The GIS website has e-form for users to report incidents or problems that occur; clogged drains, fallen trees and landslides or landslip with function to upload and download the pictures of the incidents. Reports then will be screened in advance and if the reports relate to landslides, it will be forwarded directly to local authorities. User requirement analysis was conducted using interview sessions, and the respondents were from committee member of the local resident communities and local authorities. From the analysis, it shows the GIS application in the community is important to display and distribute maps with attribute information. GIS web portal userfriendliness and effectiveness evaluation have been conducted with 20 participants. From the feedback, the web portal are deemed suitable for community engagement in landslide information crowd-sourcing and monitoring. GIS portal with GIS community based information is relevant in empowering GIS among local residents as it will increase efficiency of the residents in monitoring their surroundings and in responding to potential disaster.